De locis in homine: intento de datación - Rodríguez Alfageme, Ignacio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
Statistical study of syntactic connectives and language usage found in De locis in homine allows for a timeframe for its date.